Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan dan Implikasinya Pada Loyalitas Pelanggan Kosambi Maternal and Children Center - Azhara Ajeng Niswara (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
Kosambi Maternal and Children Center is a basic and specialized medical services with specialization in maternal and Child Services that seeks to maintain consumer loyalty by improving the quality of services and seeks to maintain consumer satisfaction in maternal and Child Health Services. This study aims to analyze the effect of service quality variables on customer satisfaction variables and their implications on customer loyalty Kosambi Maternal and Children Center. Data processing in this study using the method of Partial Least Square (PLS) with the help of SmartPLS. This study uses a quantitative approach. The method used is a survey method through questionnaires that are distributed digitally through google forms. The samples used in this study were 92 respondents taken from Kosambi Maternal and Children Center patients at random. The results of this study showed that the effect of customer satisfaction has a significant effect on customer loyalty with a T-statistic value of 7.426 ≥ 1,96 or p values of 0.000 ≤ 0,05. The quality of Service has a significant effect on customer satisfaction with T-statistic value of 5.435 ≥ 1,96 or p values of 0.000 ≤ 0,05. Service quality significantly affects customer loyalty with t-statistic value of 2.993 ≥ 1,96 p values of 0.003 ≤ 0,05.